EKSTRAK LABU SIAM DAN WORTEL TERHADAP TEKANAN DARAH PADA LANSIA YANG MENDERITA HIPERTENSI DI SASANA KARTINI KELURAHAN TOSAREN - Sutrisno, Sutrisno; Ndapajaki, Frans (LPPM STIKes SATRIA BHAKTI NGANJUK, 2021)
Hypertension is a condition of vasoconstriction of blood vessels caused by several factors such as age, gender and irregular eating patterns. The Chayote and carrot extract as non-pharmacological therapy can lower blood pressure because they contain high potassium. The purpose of this study was to determine the effect of the use of chayote and carrot extracts on blood pressure in the elderly who suffer from hypertension in Sasana Kartini, Tosaren Village. The research design used is Pre-Experimental Designs, the population is all elderly people with hypertension, which are 52 respondents, the number of samples that meet the inclusive criteria, as many as 19 respondents using purposive sampling. The independent variable in this study was the administration of chayote extract and the dependent variable was systolic and diastolic blood pressure, the instruments used for data collection research were sphygmomanometer and observation sheets. While the data processing uses the Paired Sample T-Test.